Aporie dell'integrazione europea tra universalismo umanitario e sovranismo - Ruoppo, Anna Pia (Scuola delle Scienze Umane e Sociali. Quaderni, 2021)
Aperias of European integration: between humanitarian universalism and sovereignism is the result of a study and research process that involved researchers from the University of Évora and the Centro de Investigação em Ciência Política (CICP) in Portugal and scholars from the DSU of Federico II in Naples and other prestigious Italian universities. The book, divided into three sections, deals with the conflict between universalism - understood as a philosophical principle of the Western cultural tradition and as a juridical-political principle at the basis of the integration process - and the principle of sovereignty, which instead tends to preserve the political autonomy of states in the process of integration. Contributions by: Peluso, Morfino, Cacciatore, Giannini, Rocha Chuna, Boemio, Basso, Amendola, Arienzo, Tinè, Höbel Donato, D'Acunto.